Sentinel node mapping in endometrial cancer - Bogani, Giorgio; Ditto, Antonino; Chiappa, Valentina; Raspagliesi, Francesco (Translational Cancer Research, 2019)
Sentinel node mapping in endometrial cancer staging has gained popularity among gynecologic oncology community. Although endometrial cancer represents the most common gynecological malignancy in developed countries several features of its management are still objects of debates. In particular the role of lymphadenectomy is still unclear (1). Accumulating data underlined that sentinel node mapping is not inferior to conventional lymphadenectomy (2,3). However, sentinel node mapping seems to be superior to conventional lymphadenectomy.